2005
DOI: 10.1007/s10773-005-3976-7
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Symmetry, Regge Trajectories, and the Linear Confinement in Dual QCD

Abstract: Using the magnetic symmetry structure of non-Abelian gauge theories, we analyze the flux tube formulation and its implications on the hadronic Regge trajectories and the confinement of color isocharges in magnetically condensed (with as well as without the electric excitations) QCD vacuum. Starting with the fiber bundle structure of QCD, the dual potentials are used to construct the QCD Lagrangian which has been shown to develop a unique flux tube configuration in its dynamically broken phase. The vector mass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…It is well known that monopoles and dyons emerge as essential ingredients in the dual superconductor models of QCD in context with the quark confinement problem [19][20][21][22]. It would be interesting to investigate the issue of confinement through the condensation of these topological dyons.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that monopoles and dyons emerge as essential ingredients in the dual superconductor models of QCD in context with the quark confinement problem [19][20][21][22]. It would be interesting to investigate the issue of confinement through the condensation of these topological dyons.…”
Section: Discussionmentioning
confidence: 99%
“…Following the canonical formulation of such models, linear and parallel RTs were postulated for mesonic as well as baryonic resonances. [5][6][7][8][9][10][11][12][13][14] However, in the past decade several studies have conclusively demonstrated that only a minority of RTs can be considered as linear. In addition, even these ones do not give any evidence of parallelism but instead are divergent.…”
Section: Introductionmentioning
confidence: 99%